Book review: Self-immolations of old believers (the second half of the 17th – 20th centuries) by M.V. Pulkin - Belonogova Julia Igorevna (Studia Humanitatis, 2023)
The monograph by Maxim Viktorovich Pulkin describes the history of Old Believer self-immolations. The author examines the history of the ritual suicide ideology formation, gives examples of the most famous or major self-immolations, studies the geography of the burnings. The monograph examines the responses of the state and the Church – both repressive and admonitory as well as the response of the Old Believers to them, the reaction of local authorities to the change in the policy of the supreme power in relation to schismatics. It tells about the technology of suicide, the choice of methods and places of their commissions. The main ideologists and organizers of the burnings were Old Believer mentors, to whom the main repressive attention of the authorities was directed. The elder wanderers prepared the people for the acceptance of fiery death, organised the necessary premises, preached and encouraged suicides. Special houses were built for the burnings, which were kind of outposts that protected the victims from possible escapes and from the authorities. The subject of the perception of self-immolations among the people, the attitude of believers to suicides during the faith, their justification by supporters and exposure by opponents is also considered.